Strategi Adaptasi Petani Cabai Terhadap Dampak Perubahan Iklim di Sekitar Danau Tempe - Sasmita, A. Nina; Halimah, Andi Sitti; Ambar, Abdul Azis (Universitas Galuh, 2025)
This study aims to analyze the adaptation strategies of chili farmers to climate change around Lake Tempe, focusing on the influence of climate change perception and livelihood capital. A quantitative approach was employed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to chili farmers in the study area. The results indicate that chili farmers experience significant impacts of climate change, such as shifts in planting seasons, increased pest and disease attacks, and reduced water availability. In response, farmers adopt various adaptation strategies, including crop diversification, the use of agricultural technology, and adjustments in planting schedules. The SEM-PLS model shows that climate change perception has a positive and significant effect on adaptation strategies, with a path coefficient of 0.421 (p < 0.001). Livelihood capital—which includes natural, human, physical, social, and financial assets—has a stronger influence with a path coefficient of 0.512 (p < 0.001). The R-square value of 0.612 indicates that both independent variables explain 61.2% of the variance in farmers’ adaptation strategies. In conclusion, the adaptation strategies of chili farmers around Lake Tempe are significantly influenced by their perception of climate change and the strength of their livelihood capital. These findings highlight the importance of enhancing climate literacy and improving access to productive resources to strengthen farmers’ resilience to climate change.